2019
DOI: 10.1002/2211-5463.12604
|View full text |Cite
|
Sign up to set email alerts
|

The hydrophobic C‐terminal sequence of transthyretin affects its catalytic kinetics towards amidated neuropeptide Y

Abstract: Transthyretin (TTR) is a transporter for thyroid hormone and retinol binding protein that has recently been reported to have proteolytic activity against certain substrates, including amidated neuropeptide Y (NPY). However, the proteolytic activity of TTR towards NPY is not fully understood. Here, we used fluorescence‐based assays to determine the catalytic kinetics of human TTR towards human amidated NPY. The Michaelis constant (KM) and catalytic efficiency (kcat/KM) of TTR proteolysis were 15.88 ± 0.44 μm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…It is a transporter for thyroid hormones and a retinol binding protein with very modest proteolytic activity towards very few substrates. 22 In human medicine, a reduction in plasma transthyretin could be related to severe acute phase response to thyroid diseases, but in veterinary medicine its role is not completely elucidated. 23 The few studies performed in animals have shown a lower concentration of transthyretin in 1 month diarrheic calves compared with healthy controls and reduced plasma concentrations in Mycobacterium avium paratuberculosis seropositive cows compared to healthy cattle.…”
Section: Discussionmentioning
confidence: 99%
“…It is a transporter for thyroid hormones and a retinol binding protein with very modest proteolytic activity towards very few substrates. 22 In human medicine, a reduction in plasma transthyretin could be related to severe acute phase response to thyroid diseases, but in veterinary medicine its role is not completely elucidated. 23 The few studies performed in animals have shown a lower concentration of transthyretin in 1 month diarrheic calves compared with healthy controls and reduced plasma concentrations in Mycobacterium avium paratuberculosis seropositive cows compared to healthy cattle.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitive fluorescence-based method for detecting the proteolytic activity towards Aβ and other substrates of TTR has been previously developed in our laboratory [10,17]. The pattern and the kinetic parameters of the specific cleavage of Aβ 1-42 by C. porosus and human TTRs were also demonstrated [17].…”
Section: Discussionmentioning
confidence: 99%
“…Predominant changes in TTR structure occur at the N-terminal sequence, and the N-terminal region of the avian and the reptilian are longer and more hydrophobic than that of the eutherian [5,6]. The changes influence on not only the function of TTR as distributors for TH and retinal [7,8], but also its catalytic property [9,10]. Beside functioning as TH and retinal distributors, TTR proteolytic activity towards amyloid beta (Aβ) and a few specific target proteins is evidenced for its important physiological roles in the central and peripheral nervous systems of human [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The SDS-PAGE was performed under reducing condition according to previous study ( Tangthavewattana et al, 2019 ), and immunoblotting was performed as described previously ( Kawahara et al, 2011 ). Samples were boiled with sodium dodecyl sulfate sample buffer, denatured on 13% polyacrylamide gels, transferred onto a nitrocellulose membrane, and blocked in 4% skim milk in TBS-T (0.5% Triton-X 100 with TBS) for 30 min at room temperature then washed with TBS-T three times.…”
Section: Methodsmentioning
confidence: 99%